FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Fergy Merzyana, Elizabeth Sugiarto Dermawan (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to determine the effect of growth, profitability, leverage, firm size, and institutional ownership on firm value in manufacturing companies listed in Indonesia Stock Exchange in the period 2015-2017. The sampling method used was purposive sampling with 133 data of total sampel. The result showed that growth, profitability and leverage have a significant influence on firm value, firm size have no significant influence on firm value, and institutional ownership have negatif influence on firm value.